1970
DOI: 10.1007/bf00285415
|View full text |Cite
|
Sign up to set email alerts
|

Cytological evidence on the origin of sweet potato

Abstract: The results of intensive meiotic studies, particularly of the karyology and chromosomal homology at the pachytene stage, in the sweet potato (Ipomoea batatas L.), which is a hexaploid (2 n = 90), have thrown considerable light on its origin and genome relationships. Using suitable criteria, such as relative length of chromosomes, centromere position, chromomere pattern, absence of light staining segments in one of the arms, presence of telochromomere etc., 40 of the 45 haploid chromosome complement at pachyten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 12 publications
4
37
0
1
Order By: Relevance
“…The autopolyploidization scenario assumes I. trifida to represent an autopolyploid complex, with different ploidy levels (from diploid to hexaploid) from which cultivated I. batatas derived. However, cytological and marker-based studies suggested that the I. batatas hexaploid genome may be composed of two closely related genomes and a third one from a more distant relative [19], [44]. Austin [25] postulated that the wild ancestor of I. batatas was a hybrid between I. trifida and I. triloba (allopolyploid scenario).…”
Section: Discussionmentioning
confidence: 99%
“…The autopolyploidization scenario assumes I. trifida to represent an autopolyploid complex, with different ploidy levels (from diploid to hexaploid) from which cultivated I. batatas derived. However, cytological and marker-based studies suggested that the I. batatas hexaploid genome may be composed of two closely related genomes and a third one from a more distant relative [19], [44]. Austin [25] postulated that the wild ancestor of I. batatas was a hybrid between I. trifida and I. triloba (allopolyploid scenario).…”
Section: Discussionmentioning
confidence: 99%
“…The sweet potato crop has a wide adaptability on marginal land and has the potential to alleviate malnutrition and enhance food security in the developing world (Diaz et al 1996). Sweet potato is hexaploid (2n = 6x = 90) and is highly selfincompatible (Magoon et al 1970;Ozias-Akins and Jarret 1994). More than 8,000 accessions, cultivars and breeding lines of sweet potato and nearly 26,000 accessions of other Ipomoea species are maintained at 83 gene banks in the world (Kuo 1991;Rao et al 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Morphological analysis of the related species indicates that I. trifida is the closest wild relative to sweet potato but I. tabascana is also morphologically very close (Austin, 1977(Austin, , 1987. The most compelling evidence of an allopolyploid origin is cytological data reported by Magoon et al (1970). G. Don and wild Mexican tetraploids are putative ancestors of the cultivated sweet potato.…”
Section: Botany and Physiologymentioning
confidence: 99%